Supervision of PAI Learning that Facilitates Students' Curiosity and Independence - Rizwan Martiadi; Wawan Ridwan; Citrabella Pertiwi; Ani Sri Mulyani (STAI Al-Mas'udiyah, 2026)
This article aims to examine in depth how Islamic Religious Education (PAI) learning supervision can be designed and implemented to facilitate students' curiosity and independence at the secondary school level. This study uses a library research approach by examining various relevant scientific literature from accredited national journals and international academic repositories. The results of the study show that a reflective, participatory, and transformative supervision approach is able to create a learning environment that supports students' curiosity and independence. Successful supervisory practices include collaboration between teachers and principals, the use of formative feedback, and the development of problem- and project-based learning tools. The implications of this study show the need for academic supervision training that prioritizes active learning, as well as the development of supervision indicators that include the cognitive and affective dimensions of students, especially in the context of PAI learning.